2022
DOI: 10.1371/journal.pone.0265778
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitative endovascular balloon occlusion of the aorta associated with improved survival in hemorrhagic shock

Abstract: Background Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) is controversial as a hemorrhage control adjunct due to lack of data with a suitable control group. We aimed to determine outcomes of trauma patients in shock undergoing REBOA versus no-REBOA. Methods This single-center, retrospective, matched cohort study analyzed patients ≥16 years in hemorrhagic shock without cardiac arrest (2000–2019). REBOA (R; 2015–2019) patients were propensity matched 2:1 to historic (H; 2000–2012) and conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 17 publications
1
16
1
Order By: Relevance
“…The current study is in line with other recent studies reporting a survival benefit of ED REBOA over ED RT in the US as well as in other countries . A recent meta-analysis observed a similar benefit.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The current study is in line with other recent studies reporting a survival benefit of ED REBOA over ED RT in the US as well as in other countries . A recent meta-analysis observed a similar benefit.…”
Section: Discussionsupporting
confidence: 93%
“…The current study is in line with other recent studies reporting a survival benefit of ED REBOA over ED RT in the US as well as in other countries. [8][9][10]12,14,17,18,20,21 A recent meta-analysis 22 observed a similar benefit. These are in contrast with the US study by Joseph at al 11 and 2 studies using the Japan Trauma Data Bank, 9,23 which found REBOA to be associated with higher mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of advanced endovascular techniques, REBOA has emerged as a less invasive alternative to aortic cross‐clamping for resuscitation and temporary haemorrhagic control 2 . Contemporary studies also suggest that REBOA reduces mortality in trauma patients with sub‐diaphragmatic haemorrhagic shock, 3 and is associated with improved survival in trauma patients with non‐compressible torso haemorrhage treated in a high‐volume centre 4 . Still, the indications for REBOA remain poorly defined, and there is conflicting evidence regarding the safety and efficiency of the procedure 5 .…”
Section: Introductionmentioning
confidence: 99%
“… 2 Contemporary studies also suggest that REBOA reduces mortality in trauma patients with sub‐diaphragmatic haemorrhagic shock, 3 and is associated with improved survival in trauma patients with non‐compressible torso haemorrhage treated in a high‐volume centre. 4 Still, the indications for REBOA remain poorly defined, and there is conflicting evidence regarding the safety and efficiency of the procedure. 5 We present a case of splenic artery aneurism in a pregnant woman, where REBOA was introduced late and standard surgical procedures failed to prevail, but provided a vital bridge to definitive treatment.…”
Section: Introductionmentioning
confidence: 99%